2022
DOI: 10.3389/fcell.2022.954099
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between physical cues and mechanosensitive ion channels in cancer metastasis

Abstract: Physical cues have emerged as critical influencers of cell function during physiological processes, like development and organogenesis, and throughout pathological abnormalities, including cancer progression and fibrosis. While ion channels have been implicated in maintaining cellular homeostasis, their cell surface localization often places them among the first few molecules to sense external cues. Mechanosensitive ion channels (MICs) are especially important transducers of physical stimuli into biochemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 348 publications
0
3
0
Order By: Relevance
“…Additionally, TRPV4 can also promote matrix stiffness-induced EMT. 20,30 Interestingly, the Piezo1 gene was not found to be significantly differentially expressed between the soft and stiff matrix conditions. Several genes reported to have associations with Piezo1 activity including DKK3, OBSCN, TNNT1, MAPK-10, -15, and -BP1 were, however, found to be upregulated in the stiff matrix groups.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, TRPV4 can also promote matrix stiffness-induced EMT. 20,30 Interestingly, the Piezo1 gene was not found to be significantly differentially expressed between the soft and stiff matrix conditions. Several genes reported to have associations with Piezo1 activity including DKK3, OBSCN, TNNT1, MAPK-10, -15, and -BP1 were, however, found to be upregulated in the stiff matrix groups.…”
Section: Resultsmentioning
confidence: 93%
“…Both these genes are associated with malignant progression with EDN2 involved in tumorigenesis and VIM playing a role in cell attachment, migration, and metastasis. 20 Certain other genes such as MAPK3, RAC3, JAK3, and Rho-GTPases RHOG and RHOD with associations to cancer-promoting signals were also found to be upregulated in stiff hydrogel spheroids. 43,44 Stiff substrate groups also indicated the presence of common EMT-associated genes in cancer such as CD44, COL5A3, SERPINE1, LAMC2, TGFB1, CDH13, SPARC, and certain integrins.…”
Section: Resultsmentioning
confidence: 94%
“…Fourth, this study reveals that collagen, which hitherto is ignored in pathology diagnostics for breast cancer, exhibits distinctive spatial location features in histologic patterns of TN that may inform the relevant underlying processes of breast cancer development. Studies have shown that collagen in the extracellular matrix (ECM) provides biophysical cues which can influence breast cancer progression and metastasis [ 40 ]. Collagen deposition during breast cancer progression contributes to increased matrix stiffness or elasticity, which establishes migration paths for cells.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen deposition during breast cancer progression contributes to increased matrix stiffness or elasticity, which establishes migration paths for cells. Accordingly, elevated collagen and the collagen fiber alignment relative to the breast tumor interface are risk factors for breast cancer [ 40 ]. These results indicate that the compressive stress in the tumor interior can influence the shape of the tumor mass and then influence the topographical features of the ECM, such as the formation of different spatial arrangements of collagen, which provide clues to the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). 7 Mechanical forces are transduced through mechanoreceptors which then affect cellular processes, such as proliferation and differentiation, well reviewed by Bera et al 8 Specifically, mechanical cues alter cell morphology, cell–cell interaction, and cell signaling and facilitate epithelial to mesenchymal transition (EMT) and other migratory programming. 9,10 Forces within the tumor microenvironment (TME) can be broken down and simplified into three categories: (i) shear stress, (ii) tension and strain, and (iii) solid stress and compression ( Fig.…”
Section: Introduction: the Mechanics Of Metastasismentioning
confidence: 99%